2012
DOI: 10.1038/srep00357
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of subunit influenza vaccine to skin with microneedles improves immunogenicity and long-lived protection

Abstract: Influenza infection represents a major socio-economic burden worldwide. Novel delivery methods can render influenza vaccination easier and more acceptable by the public, and importantly confer protection equal or superior to that induced by conventional systemic administration. An attractive target for vaccine delivery is the skin. Recent studies have demonstrated improved immune responses after transdermal delivery of inactivated influenza virus with microneedle patches. Here we show that immunization with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 50 publications
(87 reference statements)
7
78
0
Order By: Relevance
“…i.m. vaccination has been described to result in poor antigen-dependent T cell activation owing to the lack of APCs in muscle tissue (14). Certainly, previous studies have shown that i.d.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…i.m. vaccination has been described to result in poor antigen-dependent T cell activation owing to the lack of APCs in muscle tissue (14). Certainly, previous studies have shown that i.d.…”
mentioning
confidence: 99%
“…For instance, while most vaccinations, including DNA, are delivered via the i.m. route (13), the lower number of antigen-presenting cells (APCs) within muscle tissues has been suggested to be a factor contributing to reduced efficacy (2,5,14). i.m.…”
mentioning
confidence: 99%
“…It was demonstrated that vaccination using microneedles triggers stronger immune responses comparing to conventional injection procedures, allowing sparing of antigens. 38 Indeed, the use of microneedle-based devices for influenza vaccination is currently under clinical trials.…”
Section: A Microneedle-based Immunotolerance Approach For Msmentioning
confidence: 99%
“…Cells were washed with phosphate-buffered saline (PBS) and lysed with detergent lysis buffer (1% Nonidet P-40, 0.4% deoxycholate, 50 mM Tris-HCl [pH 8.0], 62.5 mM EDTA) on ice for 5 min. Lysates were subjected to SDS-PAGE on a 4 to 12% Bis-Tris NuPAGE gel (Invitrogen, CA).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The influenza virus surface glycoproteins hemagglutinin (HA) and neuraminidase (NA) are key mediators of the viral infectious cycle and obvious proteins of interest for novel vaccines. The majority of recent vaccine candidates focus predominantly on the immunogenic properties of the influenza virus HA, and sometimes NA, glycoprotein, seeking to utilize vector systems (1)(2)(3), adjuvants (4)(5)(6), alternative routes of immunization (7,8), and novel antigen presentation and delivery systems (9)(10)(11)(12) to increase humoral and/or cell-mediated immunity against these and other influenza virus antigens. Creating vaccines that also exploit the functional properties of the influenza virus glycoproteins represents a unique approach.…”
mentioning
confidence: 99%